Surface Water Assessment of Paghman River Basin - rahmatzai, Asadullah (Journal of Natural Sciences – Kabul University, 2020)
From a geographical standpoint, the Paghman River Basin is the primary source of both surface and groundwater consumption in Kabul City. Therefore, studying its surface water is crucial. The Paghman Basin area has steep slopes in its small topography, resulting in increased variations in temperature, rainfall, and flow regime. This study aimed to investigate the water regime of the Paghman River Basin over a specified period using statistical and hydrological methods, based on the data from the Pul-e-Sokhta and Qala-e-Malik Hydrological stations. The results show that the Paghman River's flow rate and volume in recent years are higher than in previous years; however, its overall trend is decreasing. The flow is primarily concentrated in the spring season, and the magnitude of flood flow has declined in recent years.